Vibration monitoring of structures in the light of the Polish and international requirements - Herbut Aneta; Jakubczyk-Gałczyńska Anna; Wyjadłowski Marek (Studia Geotechnica et Mechanica, 2023)
The paper concerns the wide range of strategies used to protect structures against man-made dynamic excitation. The most popular approaches applied worldwide are compared, and the main differences and similarities are summarized. The literature studies are supported by the results of the measurements performed on different types of real structures, which are sensitive and insensitive to the dynamic load. To make the conclusions more general, various types of excitation forces are examined (long-term and short-term excitations, traffic load, and loads resulting from geotechnical works). The main issue raised in the paper is the problem of unequivocal and accurate assessment of the potential structure damage, based on the different legislations. It can be seen that the application of different codes can even result in opposite conclusions about the safety of the structure.